2022
DOI: 10.1111/febs.16548
|View full text |Cite
|
Sign up to set email alerts
|

Multiple detection of both attractants and repellents by the dCache‐chemoreceptor SO_1056 of Shewanella oneidensis

Abstract: Chemoreceptors are usually transmembrane proteins dedicated to the detection of compound gradients or signals in the surroundings of a bacterium. After detection, they modulate the activation of CheA-CheY, the core of the chemotactic pathway, to allow cells to move upwards or downwards depending on whether the signal is an attractant or a repellent, respectively. Environmental bacteria such as Shewanella oneidensis harbour dozens of chemoreceptors or MCPs (methyl-accepting chemotaxis proteins). A recent study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The efficiency of our system was also evaluated with a different bacterial species, specifically the wild type Shewanella oneidensis ( So ) MR-1 strain [ 12 ]. Migration of So MR-1 cells towards malate, a documented attractant for So MR-1 [ 13 , 14 ], was quantified ( Fig 3B ). Prior to experimentation, So bacterial cells were resuspended in LM medium adjusted to pH 7.2 (Mock), in accordance with the established physiological conditions commonly employed in So chemotaxis studies [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of our system was also evaluated with a different bacterial species, specifically the wild type Shewanella oneidensis ( So ) MR-1 strain [ 12 ]. Migration of So MR-1 cells towards malate, a documented attractant for So MR-1 [ 13 , 14 ], was quantified ( Fig 3B ). Prior to experimentation, So bacterial cells were resuspended in LM medium adjusted to pH 7.2 (Mock), in accordance with the established physiological conditions commonly employed in So chemotaxis studies [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although a cooperative and interdependent relationship has been found between the two microorganisms in the mixed culture system, interspecies transfer of metabolites is generally believed to be uneasy due to the long distance. According to the literature, once one of the members produces the positive chemotactic attractant preferred by its partner, the partner will move directionally toward the attractant producing member, thereby shortening the distance and facilitating the interspecies exchange of chemicals. , In the coculture system, unlike P. denitrificans , S. oneidensis MR-1 could move due to its flagella . Bacterial chemotaxis of S. oneidensis is regulated by a well-studied two component regulatory system illustrated in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 In the coculture system, unlike P. denitrif icans, S. oneidensis MR-1 could move due to its flagella. 44 Bacterial chemotaxis of S. oneidensis is regulated by a well-studied two component regulatory system illustrated in Figure 4a. The data in Figure 4b revealed that the expression of proteins related to chemotaxis regulatory, including methylaccepting chemotaxis proteins (MCP), purine-binding protein (CheW), response regulator protein (CheY, CheR, CheB, CheY), flagellar switch protein (FliM), and flagellar motor protein (MotB) of S. oneidensis MR-1, 45 was upregulated by the coculture, indicating that chemotactic moving of S. oneidensis MR-1 was enhanced.…”
Section: Chemotaxis Moving Of S Oneidensis Mr-1 Toward P Denitrif Ica...mentioning
confidence: 99%
“…This bacterial chemotaxis provides an important competitive advantage in terms of accessibility to inert particles or living organisms (such as microalgae). They are potentially several phytoplankton–bacteria interactions that can all co-exist [ 103 , 104 , 105 ], and the biotic preservation of phytodetritus is ultimately determined by the resulting balance between attractant and repulsive effects [ 106 , 107 ].…”
Section: Effect Of the Production Of 1 O ...mentioning
confidence: 99%
“…To determine whether or not the production of 1 O 2 by phytodetritus can repel motile bacteria, a chemotaxis experiment was performed with the bacterium Shewanella oneidensis (chosen for its well-known chemotactic capacity) [ 107 , 108 ]. The results obtained showed a strong attractant effect of phytodetritus (dead E. huxleyi cells) regardless of whether they were irradiated [ 71 ].…”
Section: Effect Of the Production Of 1 O ...mentioning
confidence: 99%